Intelligent Systems in Technology of Precision Agriculture and Biosafety - Koleshko, Vladimir M.; Gulay, Anatolij V.; Polynkova, Elena V.; Gulay, Viacheslav A.; Varabei, Yauhen A. (IntechOpen, 2012)
None